Analisis Implementasi Kurikulum Merdeka dalam Mengatasi Retensi Kelas di Sekolah Menengah Atas - Aegustinawati Aegustinawati; Yaya Sunarya (Universitas Pendidikan Mandalika, 2023)
This study aims to analyze the implementation of the Merdeka Curriculum in overcoming class retention. This research used a case study method with a qualitative approach. The informants in the study were teachers and the deputy principal for curriculum at SMA Negeri 1 Tempilang, West Bangka Regency, Bangka Belitung Islands Province. Data collection techniques were conducted by interview, questionnaire distribution, observation, and documentation. This research data analysis technique used an interactive model analysis, including data reduction, data presentation, and conclusion drawing. The results of this study indicated that implementing the Merdeka Curriculum could overcome the problem of class retention. The policy's success in avoiding class retention relied heavily on the realization of planning, implementation, and assessment that prioritized essential principles in the Merdeka Curriculum. Curriculum implementation had to be carried out by referring to various regulations, instructions, and guidelines for implementing the Merdeka Curriculum in terms of planning, implementing learning, and assessing. The success of the Merdeka Curriculum in overcoming class retention required the active role of all components of education, starting from teachers, principals, related institutions, parents, and students.